Looking Back At How School-Based Curriculum Transformed Into the 2013 Curriculum - Surdyanto, Annas (CV. Pena Persada, 2020)
The Indonesian government has been working for years to find a way to escape from social problems. Through the Ministry of Education and Culture, the Indonesian curriculum has been transformed significantly. However, changes in the Indonesian curriculum always cause pros and cons among educators. This article is provided to look back at how KTSP transformed into the 2013 curriculum.